Diagnosis of Gestational, Congenital, and Placental Malaria in Colombia: Comparison of the Efficacy of Microscopy, Nested Polymerase Chain Reaction, and Histopathology (2011)
Abstract: The technical capability of different methods to diagnose Plasmodium in maternal peripheral blood, placenta, and umbilical cord blood has not been assessed in Colombia and seldom explored in other malaria-endemic regions. We designed a study to compare the technical and the operational-economical performances of light microscopy (LM), nested polymerase chain reaction (nPCR), and histopathology (HP). In maternal blood, LM had 41% sensitivity and 100% specificity and in placental blood, 35% and 100%, respectively, compared with nPCR. In placental tissue, LM had 33% sensitivity and 95% specificity; and nPCR 47% and 77%, respectively; compared with HP. Light microscopy had the best operational-economical qualification. We concluded that nPCR and HP performed better compared with LM, but field implementation of these two techniques remains a problem. Therefore, LM is recommended as the gold standard for diagnosis of gestational malaria and placental blood infection in the field.